A successful low dose spinal anesthesia in a patient with severe mitral valve stenosis for partial hip replacement surgery: A case report - Nguyen, Duy Anh; Tran, Dac Tiep; Nguyen, Ngoc Thach; Nguyen, Tien Duc (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Anesthesia for patients with mitral valve stenosis presents a great challenge for anesthesiologists. The choice of spinal anesthesia or general anesthesia for these patients is still controversial, each method has its own advantages and disadvantages. We describe the anaesthetic management for a 73-year-old female patient with a left closed intertrochanteric fracture of the femur with many concomitant diseases: atrial fibrillation, severe mitral valve stenosis, and previous cerebral stroke. The patient had successful partial hip replacement surgery under spinal anesthesia. In the preoperative period, the patient had no difficulty breathing, no chest pain, echocardiography showed severe mitral stenosis due to rheumatism with valve orifice area 0.9 cm2, left atrial enlargement, systolic pulmonary artery pressure 46 mmHg, normal ejection fraction 59% and electrocardiogram showed atrial fibrillation with ventricular response of 93 beats/minute. Left partial hip replacement surgery was successfully performed under spinal anesthesia using 5 mg 0.5% hyperbaric bupivacaine. Loss of sensation reaching the umbilicus provides adequate anesthesia for the surgery. The patient recovered without any complications and was discharged on the 14th day after surgery.